2020
DOI: 10.1177/0333102420941864
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive vagus nerve stimulation for primary headache: A clinical update

Abstract: Background Non-invasive vagus nerve stimulation (nVNS) is a proven treatment for cluster headache and migraine. Several possible mechanisms of action by which nVNS mitigates headache have been identified. Methods We conducted a narrative review of recent scientific and clinical research into nVNS for headache, including findings from mechanistic studies and their possible relationships to the clinical effects of nVNS. Results Findings from animal and human studies have provided possible mechanistic explanation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 65 publications
2
14
0
Order By: Relevance
“…Consistent with previous research (4), in PREMIUM II the migraine with aura subgroup had a more pronounced response than those without aura and appear to be particularly well suited to nVNS therapy. This clinical finding is consistent with mechanistic data from animal models, which suggest that nVNS inhibits susceptibility to and diminishes the frequency and propagation speed of cortical spreading depression, an electrophysiological phenomenon that is believed to be a major mechanism behind migraine aura (15,23,24). There is an opportunity for future research and analysis to determine whether the more prominent response of nVNS among patients with aura in this study is appreciated in other clinical settings.…”
Section: Discussionsupporting
confidence: 85%
“…Consistent with previous research (4), in PREMIUM II the migraine with aura subgroup had a more pronounced response than those without aura and appear to be particularly well suited to nVNS therapy. This clinical finding is consistent with mechanistic data from animal models, which suggest that nVNS inhibits susceptibility to and diminishes the frequency and propagation speed of cortical spreading depression, an electrophysiological phenomenon that is believed to be a major mechanism behind migraine aura (15,23,24). There is an opportunity for future research and analysis to determine whether the more prominent response of nVNS among patients with aura in this study is appreciated in other clinical settings.…”
Section: Discussionsupporting
confidence: 85%
“…Vagus nerve stimulation (VNS) has emerged as a neuromodulation strategy to provide an adjunctive therapy for medication-refractory epilepsy 1 , 2 and treatment-resistant depression 3 , 4 . Non-invasive approaches to electrically stimulate the vagus nerve have more recently emerged as an additional treatment strategy for migraine and cluster headache pain 5 , 6 . VNS may also inhibit cytokine production and modulate inflammatory conditions 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Although there is consensus that VNS affects pain processing, it remains unclear how this happens exactly [ 15 , 16 ]. In the last decades, traditional VNS is gradually being replaced by safer t-VNS, but t-VNS is predominantly applied in the treatment of headache, epilepsy and depression disorders [ 17 , 57 ]. Literature about the effect of electrical t-VNS on nociception is conflicting: while one study found an increase in pressure pain threshold and a decrease in reported pain ratings after an hour of transcutaneous stimulation of the auricular branch of the vagal nerve, another found that only most participants showed an increase in pain threshold after 30 minutes of similar stimulation [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%